Sufism Asmaran Think - abdul sani; Duratun Nafisah; Muhammad Rusydi (Sean Institute, 2024)
This Research is motivated by a negative impression of Sufism in society. The practice of Sufism as a manifestation of ihsan is often assumed and is practiced as an individual worship activity that prioritizes piety private and insensitive to the reality that is happening around him. While on the other hand, Sufism In Asmaran’s view, there are two things studied in this thesis, namely : (1) How does Sufism Asmaran think? (2) What is the Role of Asmaran, in Development of Sufism? To disclose deep field research in this study, the data collected is primary data about Sufism according to Asmaran’s views, as well as secondary data in the form of past writings discusses Sufism according to Asmaran, and relevant literature with this research. From the results of this study it was found that: Asmaran, born in Juai, Balangan, North Hulu Sungai Regency (now included in the area Balangan Regency), South Kalimantan. He is someone who educated in Islamic boarding schools and also practicing tasawuf, however Asmaran’s thoughts, themselves lean towards neo-sufism. During Asmaran’s lifetime, studied at various levels of education, both Islamic education as well as general ones. The substance of the teachings of Sufism according to Asmaran is a blend of faith, worship, good deeds, and noble character. Whole these elements must unite, faith must be reflected in the form of worship, and True worship is one that has a positive impact in the form of charitary pious and noble character. The results of this study are expected to be useful in the framework development of the reassures of Islamic education, especially in the environment Ushuluddin Faculty an Hmanities UIN Antasari Banjarmasin. And result This research is also expected to encourage the world of Islamic education to open up and provide opportunities for Sufism to take part together in order to shape humans as individual beings as well as social beings.